New species of the ground-beetles (Coleoptera: Carabidae) from North-Western China - I.I. Kabak (Кавказский энтомологический бюллетень, 2014)
Three new species of carabid beetles are described from the Xinjiang-Uygur autonomous region of China: Notiophilus altaicus sp. n. from southern part of the Mongolian Altai Mt. Range, ENE of Qinghe Town, similar to N. hyperboreus Kryzhanovskij, 1995 but differing by the coloration of body, the shape of both pronotum and elytra, and the conformation of the aedeagus; Carabus (Morphocarabus) brinevi sp. n. from southern part of the Mongolian Altai Mt. Range, ENE of Qinghe Town, occupying an intermediate position between the C. (Morphocarabus) odoratus Motschulsky, 1844 and C. (M.) tarbagataicus Kraatz, 1878 species groups; and Carabus (Ophiocarabus) nilkiensis sp. n. from the southern slopes of the Boro-Horo Mt. Range, closely related to C. (O.) ernsti Kabak, 2002 but easily differs by the body shape and the conformation of the male genitalia